An engineering approach to support user-led innovation in improving the performance of artisanal irrigation pivots in the Algerian Sahara - Abdelkrim Ould Rebai; Tarik Hartani; Marcel Kuper; Bruno Molle; Sami Bouarfa; Khalil Laib (Agricultural Water Management)
Large-scale center pivots have been imported into Algeria since the 1980s to promote cereal production in the Sahara, but these pivots did not match either user needs or smallholder farming systems. In response, local artisans designed a smaller, cheaper, more robust center pivot in an incremental open innovation process that lasted 10 years. Currently, around 35 % of the Algerian potato production is irrigated by around 40,000 artisanal center pivots, each irrigating 1 ha. The aim of the study was to design and test an engineering approach to support local innovation actors in improving the performance of the artisanal irrigation pivot. Field observations and interviews were conducted with 24 users and 10 leading artisans to analyze the innovation process and judge which improvements would be acceptable. Experiments were then conducted in situ and in the national irrigation laboratory to analyze irrigation performance and test practical adjustments to improve it. Results showed that the distribution uniformity of pivots, less than 50 %, can be improved by adjusting the position of sprinklers along the pivot laterals and fine-tuning the nozzle aperture. This study opens new perspectives for engineering approaches to support user-led innovation.